2017
DOI: 10.1177/2045893217743122
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan improves cardiac function and myocardial efficiency in rats with right ventricular failure

Abstract: Levosimendan is an inotropic and vasodilator drug, which is known to improve cardiac function in animal models of right ventricular (RV) failure. The effects of levosimendan on oxygen consumption and myocardial efficiency in the failing RV is unknown. We investigated the effects of levosimendan on RV function, myocardial oxygen consumption, myocardial external efficiency (MEE), and myocardial metabolism in rats with RV hypertrophy and failure. RV hypertrophy and failure were induced by pulmonary trunk banding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Additionally, Hansen et al. revealed that long-term treatment in the pulmonary trunk banding rat model improved RV function without increasing RV myocardial oxygen consumption leading to improved myocardial external efficiency, 29 which is consistent with the calcium sensitizing effect and emphasizes the potential therapeutic value of levosimendan therapy in PH.…”
Section: Levosimendan In Phmentioning
confidence: 75%
See 1 more Smart Citation
“…Additionally, Hansen et al. revealed that long-term treatment in the pulmonary trunk banding rat model improved RV function without increasing RV myocardial oxygen consumption leading to improved myocardial external efficiency, 29 which is consistent with the calcium sensitizing effect and emphasizes the potential therapeutic value of levosimendan therapy in PH.…”
Section: Levosimendan In Phmentioning
confidence: 75%
“…Effects on pulmonary vasculopathy was reported by attenuation of pulmonary arterial occlusive lesions, and reduced RV remodeling was demonstrated by increased capillary density, reduced cardiomyocyte size, and reduced atrial natriuretic peptide and B‐type natriuretic peptide. Additionally, Hansen et al revealed that long‐term treatment in the pulmonary trunk banding rat model improved RV function without increasing RV myocardial oxygen consumption leading to improved myocardial external efficiency, 29 which is consistent with the calcium sensitizing effect and emphasizes the potential therapeutic value of levosimendan therapy in PH.…”
Section: Levosimendan In Phmentioning
confidence: 75%
“…According to Louhelainen et al (2007) and Hansen et al (2018) , 3 mg/Kg Levosimendan (1 mg levosimendan was dissolved in 50 μL DMSO, and then diluted to 1 mg/mL levosimendan in 5%DMSO + 40%Peg400 + 5% Tween 80 + 50% water) was injected intraperitoneally 14 days after LAD, once a week, for four consecutive weeks. The solvent was injected intraperitoneally in the same way.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental data showed that Levo could attenuate pulmonary vascular remodeling in an animal model of PH, attributed to antiproliferative and anti-inflammatory effects mediated by K ATP channel activation [ 106 ]. Moreover, beneficial actions of Levo on adverse RV remodeling in experimental PH have been reported [ 107 , 108 ]. In humans, some limited evidence suggests that Levo may reduce PAP and PVR and improve RV function in patients with PAH [ 109 , 110 ].…”
Section: Therapeutic Management Of Ph-lhdmentioning
confidence: 99%